Optimizing Thermal Performance of Mini Heat Exchangers: An Experimental Analysis Using a Full Factorial Design - Sergio da Silva Franco; Álvaro Augusto Soares Lima; Alvaro Antonio Villa Ochoa; José Ângelo Peixoto da Costa; Gustavo de Novaes Pires Leite; Márcio Vilar; Kilvio Alessandro Ferraz; Paula Suemy Arruda Michima (Applied Sciences)
This study seeks to investigate the heat dissipation process in a minichannel heat exchanger, commonly employed for cooling electronic components. The analysis centers on two key factors: global thermal resistance (GTR) and the heat transfer coefficient. The innovation of this study resides in the development and analysis of a mini heat exchanger optimized using chemometric methods to achieve efficient thermal dissipation. Various conditions, including the power source, volumetric flow rate, and ambient temperature, were varied at both low and high levels to assess their impact on these variables and establish the optimal conditions for heat dissipation. The cooling of electronic components, such as processors, remains a topic of ongoing research, as the miniaturization of components through nanotechnology requires enhanced heat dissipation within increasingly smaller spaces. This experimental study identifies the optimal conditions for both GTR and the heat transfer coefficient within the examined parameters. GTR is minimized with a power of 30 W, an ambient temperature of 29 °C, and a flow rate of 2.50 L·min−1. The results indicate that electrical power was the most significant variable affecting GTR, while ambient temperature also played a determining role in the heat transfer coefficient.